Consistency and Asymptotic Normality of Maximum Likelihood Estimator in MARS Binary Response Model - Bambang Widjanarko otok (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
A good estimator has to fulfill some propertries such as unbiased, efficient and consistent. This research aims to study consistency and asymptotic normality of maximum likelihood estimator in MARS binary response model of Friedman, for predicting the continue response variable, at predictor variables, with linear combination of spline truncated.